Incidence and Predictors of Advanced Liver Fibrosis by a Validated Serum Biomarker in Liver Transplant Recipients - Mamatha Bhat; Kathleen C. Rollet-Kurhajec; Aparna Bhat; Amanda Farag; Marc Deschenes; Philip Wong; Peter Ghali; Giada Sebastiani (Canadian Journal of Gastroenterology and Hepatology)
Background and Aims. Serum fibrosis biomarkers have shown good accuracy in the liver transplant (LT) population. We employed a simple serum biomarker to elucidate incidence and predictors of advanced fibrosis after LT over a long follow-up period. Methods. We included 440 consecutive patients who underwent LT between 1991 and 2013. Advanced liver fibrosis was defined as FIB-4 > 3.25 beyond 12 months after LT. Results. Over 2030.5 person-years (PY) of follow-up, 189 (43%) developed FIB-4 > 3.25, accounting for an incidence of 9.3/100 PY (95% confidence interval [CI], 8.1–10.7). Advanced fibrosis was predicted by chronic HCV infection (adjusted hazard ratio (aHR) = 3.96, 95% CI 2.92–5.36, p < 0.001), hypoalbuminemia (aHR = 2.31, 95% CI 1.72–3.09; p < 0.001), and hyponatremia (aHR = 1.48, 95% CI 1.09–2.01; p = 0.01). LT recipients with more than 1 predictor had a higher incidence of advanced fibrosis, the highest being when all 3 predictors coexisted (log-rank: p < 0.001). Conclusions. Chronic HCV infection, hypoalbuminemia, and hyponatremia predict progression to advanced liver fibrosis following LT. Patients with these risk factors should be serially monitored using noninvasive fibrosis biomarkers and prioritized for interventions.